Japanese sake yeast supplementation improves the quality of sleep: a double‐blind randomised controlled clinical trial. (10th September 2015) - Monoi, Noriyuki; Matsuno, Ayumi; Nagamori, Yuki; Kimura, Eriko; Nakamura, Yoshitaka; Oka, Kengo; Sano, Tomomi; Midorikawa, Tatsuyuki; Sugafuji, Toshihiro; Murakoshi, Michiaki; Uchiyama, Akira; Sugiyama, Keikichi; et al.
Summary: Activation of adenosine A2a receptors in cerebral neurons induces sleep in various mammals. It was previously found that Japanese sake yeast enriched in adenosine analogues activates A2a receptors in vitro and induces sleep in mice. Here it is reported that sake yeast activated A2a receptors in a cultured human cell line and improved human sleep quality in a clinical trial. Sake yeast activated A2a receptors in HEK cells in a dose‐dependent manner with an EC50 of 40 μg mL −1, and the activation was attenuated almost completely by the A2a receptor antagonist ZM241385 with an IC50 of 73 nm . In a double‐blind placebo‐controlled crossover clinical study, 68 healthy participants ingested tablets containing either 500 mg of sake yeast powder or a placebo (cellulose) 1 h before sleep for 4 days. Electroencephalograms were recorded during sleep at home with a portable device for 4 week days. Electroencephalogram analyses revealed that sake yeast supplementation significantly ( P  = 0.03) increased delta power during the first cycle of slow‐wave sleep by 110%, without changing other sleep parameters. Sake yeast supplementation also significantly increased growth hormone secretion in the urine on awakening by 137% from 3.17 ± 0.41 (placebo) to 4.33 ± 0.62 (sake yeast) pg mg −1 creatinine ( P  = 0.03). Subjective sleepiness ( P  = 0.02) and fatigue ( P  = 0.06) in the morning were improved by sake yeast. Given these benefits and the absence of adverse effects during the study period, it was concluded that sake yeast supplementation is an effective and safe way to support daily high‐quality, deep sleep.